2005
DOI: 10.1136/jmg.2004.027631
|View full text |Cite
|
Sign up to set email alerts
|

A rare variant of the leptin gene has large effects on blood pressure and carotid intima-medial thickness: a study of 1428 individuals in 248 families

Abstract: Background: Rare mutations in the leptin (LEP) gene cause severe obesity. Common polymorphisms of LEP have been associated with obesity, but their association with cardiovascular disease has been little studied. We have examined the impact of both common and rare polymorphisms of the LEP gene on blood pressure (BP), subclinical atherosclerosis as measured by carotid intima-medial thickness (CIMT), and body mass index (BMI) in a large family study. Methods: Five polymorphisms spanning LEP were typed in 1428 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 35 publications
3
35
3
Order By: Relevance
“…Jiang et al 18 found that five SNPs positioned beyond the defined promoter region of the LEP gene showed strong association with human obesity and was transmitted to obese offspring. A recent study 19 demonstrated a strong association between a rare polymorphism in the 3 0 untranslated region of LEP and pulse pressure and carotid intimamedial thickness; the effects were not related to BMI or plasma leptin levels. Thus, differences in subject's enrolment and the presence of other variants within the LEP gene (different from the LEP-tet) should be considered to explain the relationship between LEP gene and cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 94%
“…Jiang et al 18 found that five SNPs positioned beyond the defined promoter region of the LEP gene showed strong association with human obesity and was transmitted to obese offspring. A recent study 19 demonstrated a strong association between a rare polymorphism in the 3 0 untranslated region of LEP and pulse pressure and carotid intimamedial thickness; the effects were not related to BMI or plasma leptin levels. Thus, differences in subject's enrolment and the presence of other variants within the LEP gene (different from the LEP-tet) should be considered to explain the relationship between LEP gene and cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 94%
“…The population collection strategy has been previously described in detail (Gaukrodger et al, 2005). In brief, families were ascertained via a hypertensive proband between 1993 and 1996, and any sibship in the family (in the generation of the proband or his/her offspring) greater than three members quantitatively assessable for blood pressure was collected.…”
Section: Study Populations and Ace Phenotypingmentioning
confidence: 99%
“…Blood pressure was measured using ambulatory monitoring for a period of 24 h in all subjects willing to undergo monitoring, using the A&D TM2421 monitor (Takeda Medical) according to a previously described protocol (8). A full clinical history was taken that included the subject's medical history and lifestyle factors, including consumption of alcohol and tobacco and habitual physical exercise.…”
Section: Methodsmentioning
confidence: 99%